Utilization of E-learning in The Learning Activities in Higher Education - Frank Morrison; Emmer Parges Raya; Prasad Rane Tarucan (International Journal of Science Education and Cultural Studies, 2022)
This study aims to investigate the implementation of distance learning with E-learning conducted in tertiary institutions. After the Covid-19 pandemic, E-learning became the main learning platform carried out in various universities. This research uses a qualitative approach with a type of library research. Sources of data in this study are books and research results that are in accordance with the research theme. The results of the research show that the E-learning system is the result of the development of a digital system in the world of education which aims to provide convenience for teachers and students in learning activities. Through E-learning the teaching and learning process can be carried out without face-to-face contact between the teacher and students and is no longer limited by time and place. E-learning is a solution to the problems in the world of education which are increasingly busy with various services that offer high flexibility and mobility.